The neuroprotective effect of Nasturtium officinale on learning ability and density of parvalbumin neurons in the hippocampus of neurodegenerative-induced mice model - Warit Ruanglertboon,; Ekkasit Kumarnsit,; Sukanya Dej-Adisai,; Uraporn Vongvatcharanon,; Wandee Udomuksorn, (Penerbit Universiti Kebangsaan Malaysia, 2019)
According to European traditional pharmacopeia, as well as in Chinese traditional medicine, watercress (Nasturtium officinale) has a property in enhancing physical stamina during stress condition. The aim of the study was to evaluate the neuroprotective effects of watercress extract (WCE) on dexamethasone-induced neurodegeneration in mice. Swiss albino male mice (35-40 g) were divided into 6 groups: double distilled water (DW) and normal saline solution (NSS) (DW+NSS), DW and dexamethasone (DW+DEX)-treated for 21 days, 80 mg/kg of watercress extract (WCE) and NSS (80WCE+NSS), and WCE-treated (14 days prior to and during dexamethasone treatment) at variable doses of 20 mg/kg (20WCE+DEX), 40 mg/kg (40WCE+DEX), and 80 mg/kg (80WCE+DEX). At the end of the experiment, animals were tested for spatial memory and learning ability by Morris Water Maze apparatus to determine the escape latency time (ELT), and the density of parvalbumin (PV)-immunoreactive (PV-ir) neurons in the hippocampus of the brain, using immunohistochemistry. After dexamethasone treatment, the animals had significantly lower body weight, higher ELT and reduced density of PV-ir neurons in the CA1 and CA2 regions of the hippocampus, compared to the control animals. These parameters partially improved in animals supplemented with WCE but without a dose-related pattern. This study suggests that WCE may be beneficial for neuroprotection in stress-induced neurodegeneration.